Analisis Nilai Tukar Nelayan Gill Net Di Kecamatan Sungailiat - Esy Auna; Kurniawan Salim; Endang Bidayani (Akuatik: Jurnal Sumberdaya Perairan, 2023)
Fisherman’s terms of trade is one of the indicators in determining the level of fishermen's welfare. Big potential offishery resources at Sungailiat District, , will open up the opportunity to increase local economy, to fisherman community in particular. This study aims to obtain the fisherman terms of trade of gill net fishermen and the factors that influence fishermen's terms of trade. This research was carried out in March-May 2022. This research used the interview method. Data analysis used descriptive method. The results showed that in March FTT gill net fishermen's income was 0,206, in April it was 0,208 and in May it was 0,165, so FTT income <100 which indicates that fishermen's expenditure is good for households or fishery business were bigger than the fisherman incomes, therefore shows a low level of well-being in the March-April 2022 research substance. The FTT of fishery in Maret was up to 0,238, 0,237 in April, and 0,185 in Mei, so that the fishery FTT was <100 indicates that gill net fishing gear business activities are unfavorable for fishermen. Some factors that affected the FTT of gill net fishing gear were the fisherman age, education level, number of family dependents, duration of being fisherman, fishing seaosn and the selling price of the catch from the gill net fishing gear. This study concluded that gill net fisherman FTT decreased within study substance in Maret Mei 2022.